MEMPERKUAT MANAJEMEN PEMASARAN DALAM KONTEKS PERSAINGAN GLOBAL - Priangani, Ade (JURNAL KEBANGSAAN, 2013)
In an effort to face global competition is increasingly competitive, a company or organization needs to optimize the management of targeted marketing or effective, so as to maximize the achievement benefit either profit or non-profit to the fullest. Keywords: Marketing Management, Global Competition.